Experimental characterization of briquettes produced from Eucalyptus bark with cassava starch binder - Silva, Maria Fernanda Felippe; de Carvalho Araujo, Camilla Kawane; Silva, João Vítor Felippe; Alexandre Pio, Gabriel; Silva do Rosário, Fábio; Morales, Elen; Gava, Maristela; Caraschi, José (Maderas. Ciencia y Tecnología, 2026)
Brazil has a vast area of planted forests, which makes it the second largest producer of bark as a by-product. Several alternatives have been studied for the reuse of this residue; however, little attention has been given to the use of forest residues, such as bark, in the energy sector for briquette production and to the main variables involved in this process. The aim of this work was to evaluate the viability of producing briquettes from Eucalyptus bark. The briquettes were produced and characterized according to American and Brazilian standards, evaluating two different particle sizes and the addition of cassava starch. The briquettes produced from Eucalyptus bark show potential for use, although attention should be paid to their ash content. In particular, the treatment produced with a 12-mesh granulometry and the addition of cassava starch showed the best chemical, energetic, physical, and mechanical properties. The production of briquettes from Eucalyptus bark demonstrates the feasibility of reusing forest residues for bioenergy production.